Circulating Neutrophil Dysfunction in HBV-Related Acute-on-Chronic Liver Failure - Wu, Wei; Sun, Shanshan; Wang, Yijie; Zhao, Ruihong; Ren, Haotang; Li, Zhiwei; Zhao, Hong; Zhang, Yi; Sheng, Jifang; Chen, Zhi; Shi, Yu (Frontiers in Immunology, 2021)
Background & Aims: Acute-on-chronic liver failure (ACLF) is characterized by systemic inflammation accompanied by defective anti-bacterial immunity. The role of neutrophils in immune derangement of ACLF has not been fully elucidated. This study is aimed to characterize the role of circulating neutrophils in HBV-related ACLF patients. Methods: Quantitative, phenotypic, transcriptomic, and functional alterations of circulating neutrophils were compared in ACLF and non-ACLF subjects and analysed for associations with short-term outcomes. Interventional experiments were performed to test the impact on ACLF-patient neutrophil function in vitro. Results: Circulating absolute neutrophil count was significantly increased in patients with ACLF and was an independent risk factor for 28-day mortality. ACLF-patient neutrophils differentially expressed a panel of surface markers (include TLR-1, TLR-2, TLR-4, CEACAM-1 and FPR1), as well as a distinct transcriptomic signature. ACLF-neutrophils displayed significantly impaired phagocytosis but an increased capacity to form neutrophil extracellular traps (NETs), which was more pronounced in patients with poor outcome. Healthy neutrophils mimicked functional characteristics of ACLF counterpart after co-cultured with plasma from ACLF patients. The oxidative burst and cytokine production capacities remained unchanged. Plasma GM-CSF, IL-6, IL-8, IL-10, and IP-10 levels, as well as lipopolysaccharide (LPS) concentration, were markedly elevated in ACLF patients but not DAMP molecules HMGB-1 and HSP70. Finally, a glycolysis inhibitor, 2-deoxy-glucose, reduced NET formation of ACLF patients’ neutrophils. Conclusions: Circulating ACLF-patient neutrophils exhibit alterations in number, phenotype, gene expression and function, which was associated with poor outcome and shaped by the ACLF circulatory environment. Inhibiting glycolysis can reverse neutrophil dysfunction in ACLF patients.